TCDCA inhibits pyroptosis to alleviate sepsis-related acute hepatic injury via activating TGR5 - Yuexiang, Yang; Zhiwei, Rong; Li, Baitian; Qing, Wang; Chunzheng, Liu; Zetian, Wang; Lijun, Liao (Frontiers in Immunology, 2025)
IntroductionSepsis-related acute liver injury (SALI) is a severe and life-threatening complication in septic patients, for which current therapeutic options are limited. This study aimed to investigate the potential protective role of taurochenodeoxycholic acid (TCDCA) against SALI and to elucidate the underlying mechanisms.MethodsA cecal ligation and puncture (CLP) mouse model was employed to induce SALI. The effects of TCDCA treatment were assessed by measuring serum liver injury markers (AST, ALT) and pro-inflammatory cytokines (IL-6, TNF-α, IL-1β). Liver histology, hepatocyte apoptosis, and the macrophage response were evaluated. Molecular docking was used to predict the interaction between TCDCA and the receptor TGR5, which was functionally validated using the TGR5 antagonist SBI-115. Transcriptomic analysis and Western blotting were performed to identify the key signaling pathways involved.ResultsTCDCA treatment significantly reduced serum levels of AST and ALT, suppressed the production of IL-6, TNF-α, and IL-1β, and alleviated histological liver damage, including lobular disruption, inflammation, and hemorrhage. TCDCA also decreased hepatocyte apoptosis and modulated the liver macrophage response. Molecular docking confirmed a strong interaction between TCDCA and TGR5, and the protective effects of TCDCA were abolished by the TGR5 antagonist SBI-115. Transcriptomic analysis identified 430 differentially expressed genes after TCDCA treatment, with significant enrichment in pyroptosis-related pathways. Accordingly, Western blot analysis demonstrated that TCDCA inhibited the activation of the NLRP3 inflammasome and its downstream pyroptotic proteins, an effect that was also reversed by SBI-115.DiscussionOur findings demonstrate that TCDCA confers a protective effect against SALI by suppressing hepatocyte pyroptosis, and this action is mediated through the TGR5 receptor. These results highlight TCDCA as a promising therapeutic candidate for SALI. However, further research, including clinical trials, is necessary to address potential species-specific differences and to fully elucidate its comprehensive mechanisms of action.